ANALISIS STRATEGI PENINGKATAN JIWA KEWIRAUSAHAAN BAGI MAHASISWA DI PERGURUAN TINGGI (Studi Kasus STIE Indonesia Pontianak) - Juliahir Barata; Yuana S (Jurnal Ekonomi Integra, 2023)
This research is entitled "Analysis of Entrepreneurial Spirit Improvement Strategies for College Students (STIE Indonesia Pontianak)". This study uses descriptive qualitative research methods using data collection techniques through observation, interviews, and documentation. This study seeks to describe the strategy in increasing the entrepreneurial spirit for students. The subjects in this study were the Chairperson, Head of Study Programs, Lecturers and Students. The results of this study indicate that the strategy for increasing the entrepreneurial spirit for students is through formal education, through entrepreneurship seminars and through entrepreneurial internships and motivates students to want to open a business. In every strategy, there must be inhibiting and supporting factors, as well as STIE Indonesia Pontianak has obstacles and supports. The inhibiting factors are the students themselves who are still not interested in entrepreneurship, and the supporting factor is the collaboration with the business world.